Development and assessment of non-cognitive skills among engineering students: a comparison across two universities - Vámosiné Varga, Adrienn; Burján-Mosoni, Boglárka; Rozgonyi, Erika; Homolya, Szilvia (Teaching Mathematics and Computer Science, 2025)
Non-cognitive skills, such as logical thinking and problem solving, are crucial for success in engineering fields. To assess these skills in undergraduate engineering students, we designed a targeted test comprising four different types of tasks. The study was conducted among students at the Faculty of Engineering at the University of Debrecen, and the Faculty of Mechanical Engineering and Informatics at the University of Miskolc. The aim of this paper is to analyze the test results, gather students’ feedback, and examine the strength of the relationships between deductive reasoning, diagrammatic reasoning, and algebraic thinking. Subject Classification: 97C20